2017
DOI: 10.3892/mmr.2017.6904
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin prevents the apoptosis of endplate chondrocytes by inhibiting the oxidative stress induced by H2O2

Abstract: Osteoarthritis (OA) is a degenerative disease of articular cartilage. The pathogenesis of OA remains to be fully elucidated, and several studies have found that oxidative stress is important in its pathogenesis. Baicalin is well known and has already been investigated for its role of inhibiting the oxidative stress pathway. Thus, the present study aimed to investigate the role of baicalin on the inhibition of oxidative stress in endplate chondrocytes induced by hydrogen peroxide (H2O2). Following treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
3
20
0
1
Order By: Relevance
“… 27 Moreover, several literatures demonstrated that baicalin also played a role in ameliorating OA progression. 28 , 29 …”
Section: Introductionmentioning
confidence: 99%
“… 27 Moreover, several literatures demonstrated that baicalin also played a role in ameliorating OA progression. 28 , 29 …”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a degenerative disease of articular cartilage induced by various factors. Although OA’s pathogenesis remains to be fully elucidated, it has been generally recognized that overexpression of reactive oxygen species (ROS) plays a vital role in the degeneration of articular cartilage [ 26 ]. Submillimolar concentrations of H 2 O 2 can induce inhibition of the extracellular matrix (ECM) synthesis, chondrocyte apoptosis, lipid peroxidation, and inflammatory cytokines overproduction, and lead to the matrix metalloproteinase (MMPs) formation [ 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 -mediated oxidative stress can enhance ROS and lipid peroxidation levels in chondrocytes. Previous studies have shown that chondrocyte apoptosis induced by oxidative stress was responsible for the development of OA [ 26 , 30 , 31 ]; lipid peroxidation could be induced by ROS and caused significant tissue damage in degenerative osteoarthritis [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xing et al (23) concluded that BA protects chondrocytes by inhibiting NF-κB signaling pathways (23). Moreover, it was reported that BA significantly inhibited the oxidative stress and decreased cell apoptosis (25). The HIF-1α pathway generally involves chondrogenesis and cartilage formation of chondrocytes (16).…”
Section: Baicalin Promotes Extracellular Matrix Synthesis In Chondrocmentioning
confidence: 99%